Histopathologic Characteristics of Internal Auditory Canal Diverticula. Issue 6 (July 2019) - Muelleman, Thomas; Maxwell, Anne K.; Lopez, Ivan; Linthicum, Fred; Ishiyama, Akira; Ledbetter, Luke; Lin, James; Staecker, Hinrich; Miller, Mia
Abstract : Hypothesis: We hypothesize that internal auditory canal (IAC) diverticula occur independent of otosclerosis as demonstrated by temporal bone histopathology. Background: Diverticula at the anterior-inferior aspect of the IAC have been described histologically in the setting of cavitary otosclerosis. Recent radiographic studies show the prevalence of IAC diverticula that is higher than what can be accounted for by cavitary otosclerosis alone. Methods: We examined hematoxylin and eosin temporal bone histopathology slides with otosclerosis involving the IAC. We also examined bones from normal hearing subjects with normal histologic findings. Temporal bones were included if donors were more than 18 years of age at time of death and adequate horizontal cuts were available to evaluate the area of interest. Results: IAC diverticula were found in 33 of 47 (70%) temporal bones with IAC otosclerosis and in 5 of 20 (25%) normal temporal bones. The difference in mean pure tone averages (PTA) in the normal temporal bones with (PTA 7.3 ± 7) and without (PTA 8 ± 2) diverticula was not statistically significant ( p  = 0.86). Conclusion: IAC diverticula which have been previously demonstrated to occur in the setting of cavitary otosclerosis can also occur independent from otosclerosis. Subjects with diverticula but without other temporal bone pathology have normal hearing thresholds.